Law EnforcementAgainst Dangerous Pharmaceutical Preparations in the National Health System - Dian Puspito Rini; Adnan Hamid; Pattharawadee Rangsimanop (Journal Evidence Of Law, 2025)
Cosmetic preparations are ingredients that can be used on parts of the body that change a person's appearance. In Indonesia, the discovery of dangerous cosmetic preparations is rampant, based on several Press Releases submitted by the POM Agency. The rise of the discovery of dangerous cosmetic preparations has had a great impact on the health system in Indonesia. The a need for law enforcement against dangerous cosmetic preparations to improve the health system in Indonesia and to achieve the highest degree of health for the community. The purpose of research is to dig up and find a fact that has not existed before. The method used is qualitative literature research. The results of the surveillance research on cosmetic preparations still face obstacles due to limited human resources, large surveillance areas, and the complexity of supervision. The results of the study are the punishments given to business actors who commit cosmetic crimes, with the punishment imposed on the perpetrators being relatively light, so that they do not cause a deterrent effect for business actors. Law enforcement against dangerous cosmetic preparations in Indonesia has not had a deterrent effect on business actors and does not cause fear of committing violations, so that it can be said that it has not been able to realize the highest optimal level of public health.